(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
An educational experience based on the proposal of the American psychologist Ronald Schmeck. In the race of Early Childhood Education this model was applied in the course of Research Methodology, considering that this subject requires the development of a high cognitive structure, able to establish analysis, relationships, comparisons for hypotheses, interpretations of data and making conclusions constructs. Whereas the students entering this degree program come from a vulnerable context, the model of information processing is strengthened, enabling them to structure order of their thought and from there their cognitive bases are supported with stimulations learning processes developed in the classroom. Evidence of these achievements is reflected in a specific test where the skills that students can master in this subject are determined.